The impact of Nd3+/La3+ substitution on the cation distribution and phase diagram in the La2SrAl2O7-Nd2SrAl2O7 system - I. A. Zvereva; E. A. Tugova; V. F. Popova; O. I. Silyukov; I. A. Minich (Chimica Techno Acta)
The effect of isovalent cation substitution of lanthanum atoms in the structure of La2SrAl2O7 oxide, and phase equilibria (solidus-liquidus curves) in the binary system La2SrAl2O7-Nd2SrAl2O7 were studied. It was found that Nd3+ substitution for La3+ has effect on the structure of La2SrAl2O7 in respect of the character of cation distribution in the solid solution La2–xNdxSrAl2O7 from statistically disordered to the ordered one where strontium cations predominantly occupied the rock-salt layers, as reflected by the solidus-liquidus lines.